The Utilization of New Media in Supporting Digital Literacy during the Covid-19 Pandemic: A Phenomenological Study of the Use of "Digilib Praja" - Idza, Allisa Akhidatul; Putri, Shinta Hartini; Sugiarta, Nugraha (Indonesian Journal of Librarianship, 2022)
Abstract Background: The policy of using smartphone in order to support learning process during Covid-19 Pandemic has demanded IPDN’s Library to innovate its digital literacy services through Digilib Praja, a new media that is android based. Purpose: The research purpose is to perceive Praja’s experiences and motives in order to support digital literacy by utilizing Digilib Praja Application in the midst of the Covid-19 Pandemic. Method: The method used in this study is qualitative and used the concept of phenomenology by Alfred Schutz. The research object is new media of Digilib Praja. The data was collected by interviewing, observing, and documenting. Result: The research finding shows that Praja’s experience after utilizing Digilib Praja is they attained various benefits such as they feel easy to find the needed books, they feel easy to gather information, and they are familiar with electronic books. Moreover, the because-motives that are more likely to be Praja’s reasons in utilizing Digilib Praja are because it is easy to find the library collection books and they have a hard time to finish their assignments. Conclusion: This study suggests that there are five because-motives namely factor of the easiness to find library collections, factor of the difficulty to finish college assignments, factor of the difficulty to find references/ source of information, factor of the inadequate facilities in IPDN Regional Campus’ libraries, and factor of the difficulty find books in library shelves. There are three in-order-to motives, which are to support digital literacy, to obtain support for technological developments and to seek entertainment collections. Praja depict Digilib Praja application as a tool, which facilitate them to develop their digital literacy ability Keywords: Digilib Praja; Phenomenology; Digital Literacy; New Media